The study on risk assessment of carotid plaques in the Northern Chinese population based on LASSO regression - Yuan, Kun; Li, Chongjian; Chu, Junmin; Huang, Yilin; Song, Jiayi; Dong, Liguang; Yang, Ying; Wang, Hongyu; Liu, Jinbo; An, Xinhua; Tian, Xiaoyuan; Mu, Lin; et al. (Scientific reports, 2025)
Early identification and management of asymptomatic carotid plaques can reduce the risk of cardiovascular and cerebrovascular events. This study aimed to explore the factors that affect carotid plaques in the Northern Chinese population and construct a nomogram for risk assessment to identify high-risk populations for carotid artery plaques. A cross-sectional study on cardiovascular factors was conducted in Shijingshan District, Beijing, from January 2022 and August to September 2023, targeting individuals aged 18 years and above. Carotid plaques were assessed via carotid ultrasound. LASSO regression was used for feature selection, logistic regression was employed to analyze risk factors, and a risk assessment nomogram was also developed.. The performance was evaluated using the area under the receiver operating characteristic curve (AUC), and the calibration was assessed through the Hosmer‒Lemeshow goodness-of-fit test. The study included a total of 828 subjects, with 558 in the normal group and 270 in the carotid plaque group. Thirty-three risk factors were included in the LASSO regression analysis as independent variables for screening. The results of the adjusted multiple logistic regression analysis show that age (OR = 6.81, 95% CI:4.371–10.758), unmarried marital status (OR = 3.475, 95% CI: 1.927–6.554), current smoking (OR = 2.318, 95% CI: 1.519–3.553), hypertension history (OR = 1.794, 95% CI: 1.123–2.860), dyslipidemia history (OR = 1.920, 95% CI: 1.149–3.215), systolic blood pressure (SBP) (OR = 1.014, 95% CI: 1.004–1.024), GLU (OR = 1.135, 95% CI: 1.017–1.272), and malondialdehyde (MDA) (OR = 1.014, 95% CI: 1.003–1.025) were associated with an increased risk of carotid plaques.In contrast, higher education levels were associated with a lower risk of carotid plaques, with education level (3) (OR = 0.436, 95% CI: 0.208–0.917) and education level (4) (OR = 0.348, 95% CI: 0.170–0.718) indicating a protective association. The constructed nomogram Risk assessment had an AUC of 0.850 (95% CI: 0.823–0.877) and demonstrated good calibration (χ 2 = 13.973, P = 0.08246). By integrating age, education level, marital status, current smoking, hypertension history, dyslipidemia history, SBP, GLU and MDA, we developed a high-performance nomogram for assessment., which may be helpful for the early detection and prevention of carotid plaques in the general population. Further studies may be useful to validate the applicability in different regions and populations.